Prevalence of Overweight and Obesity in Turkey. (September 2015) - Erem, Cihangir
Abstract: Obesity is a major public health problem affecting an important proportion of the Turkish population. The prevalence of obesity has significantly increased among adult Turkish population over the past 20 years. In 1990, 18.8% of the adult population was obese (28.5% among women and 9% among men), and the prevalence increased to 36% in 2010 (44% among women and 27% among men). From the data, we found that the prevalence of obesity in Turkey has increased steadily from 1990 to 2010 in both genders. Adult obesity-associated risk factors are age, gender, hypertension, hyperlipidemia, smoking cessation, alcohol consumption, high household income, low education level and physical activity, occupation, marital status and a family of selected medical conditions (e.g. obesity, diabetes and hypertension). To control obesity, necessary precautions should urgently be taken. The precautions include serious public health education encouraging a well-balanced diet and increasing physical activity.